Root Maturation in Teeth Treated by Unsuccessful Revitalization: 2 Case Reports - Žižka, Radovan; Buchta, Tomáš; Voborná, Iva; Harvan, Luboš; Šedý, Jiří (Journal of endodontics, 2016)
This article deals with the unusual course of failed revascularization/revitalization cases. Up to this date the evidence of success and failure rates of revascularization/revitalization treatment is scarce. These case reports present "unsuccessful" revascularization/revitalization treatment of permanent immature teeth with apical periodontitis. Although the teeth were treated by protocol suggested by the American Association of Endodontists and the symptoms disappeared, maturation of teeth continued, and periapical lesion was reduced, the teeth went symptomatic during the follow-up. Subsequently, regular root canal treatment was performed. Despite chronic infection that was probably left inside the root canal after a disinfection protocol, the secondary aims of the treatment were achieved even when the primary ones were not. The possible causes of failures of revascularization/revitalization treatment and their prevention are discussed.
Keywords: Root Canal Preparation; Root Canal Therapy; revitalization; řezáky; revascularization; Humans; nekróza zubní dřeně; immature tooth; hrot zubního kořene; fyziologická neovaskularizace; dítě; Root Canal Filling Materials; Child; root maturation; Female; výplňové materiály kořenových kanálků; Tooth Root; Apexification; lidé; Tooth Apex; Incisor; Periapical Periodontitis; Apical periodontitis; ženské pohlaví; terapie kořenového kanálku; prostředky na výplach kořenových kanálků; Male; Dental Pulp Necrosis; zubní kořen; Czech Republic; Root Canal Irrigants; preparace kořenového kanálku; Česká republika; mužské pohlaví; Treatment Failure; periapikální periodontitida; Neovascularization, Physiologic; neúspěšná terapie; apexifikace